2021
DOI: 10.1155/2021/2452057
|View full text |Cite
|
Sign up to set email alerts
|

Antidyslipidemic Potential of Water-Soluble Polysaccharides of Ganoderma applanatum in MACAPOS-2-Induced Obese Rats

Abstract: Increased consumption of high-calorie foods leads to obesity usually associated with metabolic disorders including diabetes, hyperglycemia, and dyslipidemia. Ganoderma applanatum is a nonedible mushroom traditionally used in West Cameroon for the treatment of many diseases including hypertension, diabetes, and hepatitis. This study was designed to investigate the antidyslipidemic potential of water-soluble polysaccharides of G. applanatum in MACAPOS-2- (maize, cassava, palm oil, and sugar) induced obese rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In comparison to the NC group, the M group showed an increase in all serum parameters, with HDL-C increasing in the HY group and TC, TG, and LDL-C decreasing in the LY and HY groups compared to the M group. Research has shown that increased HDL-C levels and decreased TC and TG levels can reduce the risk of cardiovascular disease [ 25 ]. Therefore, the findings suggest that LH could provide cardiovascular advantages.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to the NC group, the M group showed an increase in all serum parameters, with HDL-C increasing in the HY group and TC, TG, and LDL-C decreasing in the LY and HY groups compared to the M group. Research has shown that increased HDL-C levels and decreased TC and TG levels can reduce the risk of cardiovascular disease [ 25 ]. Therefore, the findings suggest that LH could provide cardiovascular advantages.…”
Section: Resultsmentioning
confidence: 99%
“…Kanwal et al [ 27 ] mixed the fruit body powder of Dictyophora indusiata with boiling water at a ratio of 1:30 ( w / v ) and then extracted it for 2 h to obtain crude polysaccharide (DIP). Mfopa et al [ 28 ] extracted the dried and crushed fruiting body powders of Ganoderma applanatum in boiling water for 3 h and treated them with 95% ethanol at 4 °C for 24 h to obtain polysaccharides. Wang et al [ 29 ] treated the dried Poria cocos Wolf powder with petroleum ether for 24 h at room temperature, extracted them with a ratio of 20:1 (mL/g) in boiling water for 2 h, and then precipitated with four volumes of ethanol at 4 °C to obtain Poria cocos Wolf polysaccharide (PCP-H).…”
Section: Extraction Methods Of Efpsmentioning
confidence: 99%
“…The results showed that TC and TG concentrations in diabetic mice were reduced by 18.8% and 12.0%, respectively, after EPS treatment, and the reduction in LDL-C, HDL-C, and atherogenic index was also observed. Mfopa et al [ 28 ] investigated the antilipidemic potential of Ganoderma applanatum polysaccharides (GAP) in obese rats. The results revealed that GAP intervention could reduce the rate of food intake in obese rats and thus delay the rate of weight gain, and GAP intervention at different doses could significantly reduce TC, TG, and LDL-C levels.…”
Section: In Vivo Bioactivity Of Tfpsmentioning
confidence: 99%
“…Therefore, the dietary inclusion of polysaccharides could reduce calorie intake. Moreover, due to their complex special structure, polysaccharides are characterized by great fat-binding capacities, which leads to the increased excretion of dietary or endogenous fatty acids ( 73 ). Polysaccharides can bind bile acids in the intestine to enhance its excretion, thus enabling new bile acid synthesis in the liver and consuming more cholesterol ( 74 ).…”
Section: Polysaccharides Play Vital Roles In the Physiological Status...mentioning
confidence: 99%